Characterization and kinetic study of activated sludge process in palm oil mill effluent (POME) treatment - Wun, Wee Long (2020)
Due to the more stringent discharge standard of the environmental regulation, many palm oil mills are struggled to meet the compliance. Thus, the polishing treatment plant for palm oil mill effluent (POME) discharge are developed and implemented to enhance the biological treatment process after the conventional ponding system Nevertheless, the biological treatment process yet to achieve the required discharge standard due to the inappropriate system design. Thus, characterization of POME and kinetic study of POME treatment was conducted to obtain the appropriate information for the POME treatment system design. In this study, physical composition determination was carried out through the drying and ignition process of anaerobic treated POME sample for solids contents analysis and particle size distribution (PSD) analysis was conducted via filtration process by using different pore size of filter paper (namely 2 µm, 5 µm, 10 µm, 20 µm, 50 µm and 100 µm). There was about 46% of total fixed solids (TFS) had been found in total solids (TS) of POME and 63% of TS was contributed by solids particle with particle size of 20-50 m and 50-100 m. Besides, major contribution of chemical constituent in POME were biochemical oxygen demand (BOD) and chemical oxygen demand (COD). Hence, ultimate biochemical oxygen demand (L0) was estimated through BOD kinetic study methods, namely Least Square Method, Fujimoto Method, Thomas Graphical Method, Log Different Method and Method of Moment after conducting the 7-days BOD testing of anaerobic treated POME sample. While COD fractional of POME, namely biodegradable COD (bCOD) and soluble readily biodegradable (srbCOD) were determined concurrent with the kinetic study of activated sludge process in POME treatment. From the study, uBOD, bCOD and srbCOD was found at 1,139 mg/L, 1,235 mg/L and 719 mg/L, respectively. In order to investigate the effect of operating conditions on POME treatment using activated sludge, the selected operating conditions in this study were initial pH, hydraulic retention time (HRT), organic loading rate (OLR), initial mixed liquor volatile suspended solids (MLVSS), solid retention time (SRT), and molasses concentration added as a carbon source. The efficiency of activated sludge was evaluated by treating the anaerobic treated POME under aerobic conditions based on the Food to Microorganism (F/M) ratio of 0.3 kg BOD/kg MLVSS.day. The best operating condition for initial pH, HRT, OLR, initial MLVSS, SRT, and molasses concentration were found to be 6.5 ± 0.1, 48 hours, 0.31 g BOD3/L.day, 2000 ± 200 mg/L, 10 days and 50 mg/L, respectively at the removal of chemical oxygen demand (COD) and biochemical oxygen demand (BOD) in POME ranging from 62 - 68% and 60 – 65% respectively. By using the result of characterization and optimum operating condition of POME treatment, kinetic study of POME treatment by activated sludge system were carried out to obtain the kinetic parameters for the POME treatment. From this kinetic study, the kinetic parameters for COD and BOD basis had been determined for maximum yields coefficient (Y), endogenous decay coefficient (kd), maximum specific substrate utilization rate (k) and half-velocity constant (Ks) at 0.2369 mg VSS/mg COD, 0.1060 day-1, 2.2717 day-1 and 758.7705 mg/L for COD basis whilst the kinetic parameters value for BOD basis were 0.6718 mg VSS/mg BOD3, 0.0658 day-1, 1.4136 day-1 and 556.1526 mg/L, respectively. These kinetics parameters were important in designing the POME treatment system that is able to meet the standard as the design using DOE default value has been shown to under-design and failure to meet the required standard.